Level of women-friendly care provision among mothers in immediate post-partum period at public hospitals of Southeast Ethiopia: a cross-sectional study - Chala Kene; Yohannes Tekalegn; Diriba Dibaba; Mujib Abdella; Genet Fikadu; Daniel Atlaw; Degefa Gomora; Girma Geta; Kenbon Seyoum; Sintayehu Hailu; Neway Ejigu; Biniyam Sahiledengle; et al. (BMC, 2022)
Abstract Background The women-friendly care approach focuses on women's rights to have access to quality care for themselves as individuals, as mothers, and for their infants. However, access to quality health services is not guaranteed for many women, particularly in low and middle-income countries. Hence, this study aimed to assess the level of women-friendly care provision and associated factors among mothers in the immediate post-partum period at public hospitals of Bale Zone, Southeast Ethiopia 2021. Methods An institutional-based cross-sectional survey was employed among mothers in the immediate post-partum period in public hospitals of Bale Zone from March 1-30, 2021. A total of 363 mothers were recruited by systematic random sampling technique in this study. Data was collected through pre-tested structured questionnaires. A 21-verified questionnaire was used to measure the outcome variable. The data were entered into Epi Data version 4.6.2.0 and exported to the statistical package of social science version 26.0 for analysis. A variable with a P value of less than 0.25 in the bi-variable binary logistic regression model was transferred to a multivariable binary logistics regression model. Hosmer and Lemeshow's goodness of fit model was checked. Adjusted odds ratio with 95% confidence intervals were used to estimate the strength of association between the outcome variable and independent variables. A p-value less than 0.05 was considered as significantly associated. Results The level of women-friendly care provision among mothers in immediate post-partum at public hospitals of Bale Zone was found to be 61% [95% confidence interval (55.73-66.04)]. Being prim para mother [Adjusted odds ratio = 1.88(1.07-3.33)], having planned pregnancy [Adjusted odds ratio = 1.94(1.04-3.63)] and staying at a health facility after delivery [Adjusted odds ratio = 4.8(1.71-13.39)] were found to be statistically significant predictors of level of women-friendly care provision. Conclusion The women-friendly care provision among mothers in the immediate post-partum period in this study area was found to be low against most of the pre-existing findings. Strong counseling on planned pregnancy and staying at a health facility after delivery is recommended.